2010
DOI: 10.1177/1721727x1000800202
|View full text |Cite
|
Sign up to set email alerts
|

IL-34 a Newly Discovered Cytokine

Abstract: In this study we describe some biological effects of IL-34, a newly discovered cytokine. We show that 11-34 stimulates monocyte cell viability and directly modulates the number and function of monocytes and regulates myeloid cell growth and differentiation. Moreover, since IL-34 in mice is involved in osteoporosis, an antagonist of this cytokine could be beneficial for the treatment of this disease.Cytokines are immune-regulatory proteins (1-4) and they induce inflammation in vivo, based on recruitment of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In some experimental animals, samples 24 h post-allergen challenge, there is an increased proportion of activated CD4+ T cells and in situ hybridization has revealed increased numbers ofcells expressing mRNA for IL-4, IL-5, and GM-CSF, but not IL-2, IL-3 or IFN-gamma (27). Consistent with this, the IL-4 and IL-5 mRNA are predominantly confined to T cells (28).…”
supporting
confidence: 61%
“…In some experimental animals, samples 24 h post-allergen challenge, there is an increased proportion of activated CD4+ T cells and in situ hybridization has revealed increased numbers ofcells expressing mRNA for IL-4, IL-5, and GM-CSF, but not IL-2, IL-3 or IFN-gamma (27). Consistent with this, the IL-4 and IL-5 mRNA are predominantly confined to T cells (28).…”
supporting
confidence: 61%
“…Interestingly, human lesions contain CD4+ T cells reactive to the diseaserelated antigens associated with oxidized LDL (32). The atherosclerotic lesion contains cytokines that promote a T-helper I response, inducing activated T cells to differentiate into T-helper 1 effector cells (33)(34)(35). These cells amplify the local inflammatory activity by producing proinflammatory cytokines such as IFN-and CD40 ligand (CD40L, CDI54), which contribute importantly to plaque progression.…”
Section: Interleukin-/8mentioning
confidence: 99%
“…On the other hand, many studies have confirmed the influence of psychological factors on different aspects of the immune system, important in the process of tumor development (12). Cellular-mediated and humoral-mediated responses are affected in general psychiatry traumatic disorders, as is the production of cytokines (13)(14)(15). The hypothalamic-pituitaryadrenal axis responds to several compounds, such as inflammatory cytokines: tumor necrosis factor (TNF)-u, interleukin-I (lL-I) alpha and beta, interleukin-18, interleukin-33 and interleukin-6 (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%